Karakterisasi Varietas Unggul Pisang Mas Kirana dan Agung Semeru di Kabupaten Lumajang - P.E.R. Prahardini; nFN Yuniarti; Amik Krismawati (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2010)
The Characterization of Two Superior Varieties of Banana from Lumajang Regency East Java. Lumajang regency is one of the banana production centre in East Java having highdiversity of banana germ plasm. There are 33 cultivars of banana germ plasm in the regency, consist of table fruit and plantain. The superior variety in Lumajang Regency are Agung Semeru (Musa x paradisiaca) as plantain and Mas Kirana (Musa acumunata) as fresh table fruit varieties. Those variety can grow well at 450-650 m above sea level. The objective of this study were to make inventory and exploration banana plants with respect to the information on the condition. Inventory and exploration were conducted at two Regency, i.e. Senduro and Pasrujambe from Mei 2006 until March 2007. The aim of this study were to identify, characterize, and inventarize of banana tree and use as reference characteristics of banana tree. The characteristic of banana’s Agung Semeru variety could be seen by the colour of pseudostem (light red), the uniqueness of fruit set, number of sucker per cluster (only 1-2 suckers per cluster), the size of the finger (33-36 cm long) and 19 cm around) and the number of hand per bunch (only 1- 2 hand per bunch) with the weight around 10-20 kg/bunch. Superior characteristics of the Agung Semeru variety were the thickness of fruit skin, the long period of fruit storage (3-4 weeks after harvesting) and the sweetness of fruit flesh. Even though the skin changes from yellow to black, the flesh still could be consume, because it doesn’t become soft. This variety could be used for the raw material of small and middle home industries. The characteristic of banana Mas Kirana variety could be seen by the colour of pseudostem (brownish-red), number of sucker per cluster (only 2-3 suckers per cluster), the size of the finger was small and prefered by the consumer with yellowish colour, the weight around 11-13 kg/bunch. Superior characteristics of the Mas Kirana variety were sweetness, fresh and crispy of fruit flesh, beside those character also could be used for banana’s cakes and had short period of production. In additions those varieties were also resistant to the Sygatoka disease compared to other plantain cultivars. AbstrakKabupaten Lumajang Jawa Timur, merupakan salah satu wilayah yang mempunyai keragaman plasma nutfah pisang. Di daerah ini terdapat 33 plasma nutfah pisang yang terdiri atas pisang sebagai buah meja dan pisang olahan. Varietas unggul pisang di Kabupaten Lumajang adalah Agung Semeru (Musa paradisiaca) sebagai pisang olahan dan Mas Kirana (Musa acumunata) sebagai buah segar. Kedua varietas pisang tersebut tumbuh pada ketinggian 450-650 m dpl. Eksplorasi dilakukan dengan cara mengumpulkan dan mengidentifikasi tanaman, bentuk tumbuhan, dan habitat. Kegiatan eksplorasi dilakukan di dua kecamatan, yaitu Senduro dan Pasrujambe, pada bulan Mei 2006 hingga Maret 2007. Tujuan kegiatan ini adalah untuk mengidentifikasi, menginventarisasi, dan mengkarakterisasi tanaman pisang, sehingga dapat disusun berbagai karakter tanaman. Karakteristik pisang varietas Agung Semeru terlihat dari warna batang (merah terang), pembentukan buah yang unik, jumlah anakan 1-2 anakan/rumpun, di samping itu ukuran buah besar (keliling buah 19 cm) dan panjang (33-36 cm), jumlah sisir 1-2 sisir/tandan dengan bobot 10-20 kg/tandan. Keunggulan lain dari pisang varietas Agung Semeru adalah kulit buah tebal sehingga tahan disimpan 3-4 minggu setelah petik dan rasa buah manis. Walaupun kulit buah sudah kehitaman tetapi daging buah tetap enak dikonsumsi karena tidak lembek. Karakteristik pisang varietas Mas Kirana terlihat dari warna batang (merah kecoklatan), jumlah anakan 2-3 anakan/ rumpun, ukuran buah kecil yang disenangi konsumen, dan berwarna kuning bersih. Keunggulan varietas Mas Kirana adalah rasa daging buah manis, segar, dan teksturnya renyah, dapat dijadikan bahan baku industri olahan berupa tepung pisang dan sale, umur relatif genjah dengan produktivitas 11- 13 kg/tandan. Kedua varietas tersebut tahan penyakit bercak daun dibandingkan dengan kultivar pisang lainnya.